ADOPTION OF MOBILE BANKING SERVICES: AN EMPIRICAL EXAMINATION BETWEEN GENERATION Y AND GENERATION Z IN THAILAND - Athapol Ruangkanjanases; Suphitcha Wongprasopchai (Bina Nusantara University, 2018)
The purpose of this study is to identify the significant factors that affect the adoption of mobile banking services, by conducting an empirical investigation on generation comparison, between Gen Y and Gen Z in Thailand. To test the framework, descriptive analysis, correlation analysis, collinearity analysis, and multiple linear regression analysis were applied to the primary data, which consists of 400 surveys collected from mobile banking users in Gen Y and Gen Z in Thailand. The results show that compatibility, perceived usefulness, and self-efficacy are significantly and positively affect customer intention to adopt the services in both generations. Interestingly, social influence has significantly affected adoption of mobile banking only in Gen Z.